Credibility, peer review, and Nature, 1945–1990 - Baldwin, Melinda (Notes Rec R Soc Lond, 2015)
This paper examines the refereeing procedures at the scientific weekly Nature during and after World War II. In 1939 former editorial assistants L. J. F. Brimble and A. J. V. Gale assumed a joint editorship of Nature. The Brimble–Gale era is now most famous for the editors' unsystematic approach to external refereeing. Although Brimble and Gale did sometimes consult external referees, papers submitted or recommended by scientists whom the pair trusted were often not sent out for further review. Their successor, John Maddox, would also print papers he admired without external refereeing. It was not until 1973 that editor David Davies made external peer review a requirement for publication in Nature. Nature's example shows that as late as the 1960s a journal could be considered scientifically respectable even if its editors were known to eschew systematic external peer review.